Effect of COVID-19 Pandemic Lockdowns on Body Mass Index of Primary School Children from Different Socioeconomic Backgrounds - Ludwig Piesch; Robert Stojan; Jochen Zinner; Dirk Büsch; Katharina Utesch; Till Utesch (SpringerOpen, 2024)
Abstract Background Childhood obesity is associated with various health outcomes. Restrictive measures to contain the spread of the Coronavirus Disease 2019 (COVID-19) pandemic, like lockdowns and school closures, affected children's daily structure, physical activity, dietary habits, and sleep quality, possibly exacerbating risk factors for childhood obesity and higher body mass index (BMI) in children. Poor socioeconomic conditions may have led to relatively higher risk for elevated BMI levels following pandemic measures. In this study, the impact of measures related to the COVID-19 pandemic on the BMI of third graders was investigated regarding children's socioeconomic background (SEB). Methods Data from 41,728 children (8.84 ± 0.56 years, 20,431 female) were collected in the context of a cohort study. Children were tested either before the pandemic (preCOVID: Sept2017-March2020, n = 26,314), or following the first (postLDI: Aug2020-Dec2020, n = 6657) or second lockdown in Germany (postLDII: Aug2021-Jan2022, n = 8757). SEB was based on the official school type classification of the state of Berlin. Outcome was BMI standard deviation scores (SDS). Results Significant effects of Time and SEB revealed elevated BMIs in postLDI (M = 0.23, p = 0.011) and postLDII (M = 0.22, p = 0.011) compared to preCOVID (M = 0.17) cohorts and higher BMIs for children with lower SEB (b = − 0.13, p < 0.001). A significant Time × SEB interaction indicated that the effect of SEB on children's BMI increased in response to lockdowns, especially in postLDII (b = − 0.05, p = 0.006). Results suggest that the COVID-19-related measures lead to increased BMI in children, and that children of lower SEB were at particular risk for higher BMIs following lockdowns. Conclusions These findings highlight the dependency of children's BMI on societal circumstances. Over the course of two lockdowns in Germany, children have experienced BMI increments, particularly in low socioeconomic areas. Authorities are called into action to counteract increasing rates of childhood weight by promoting physical activity of children and establishing related post-pandemic offers.